Prevalence of sleep disturbances and factors associated among school going children in Uganda, a cross-sectional study - Baluku Reagan Innocent; Oriokot Lorraine; Elly Katabira; Martha Sajatovic; Abbo Catherine; Kaddumukasa Mark (Sleep Epidemiology)
Background: Sleep disturbances greatly impact children's academic performance and social well-being. This study set out to determine the prevalence of sleep disturbances and factors associated among school going children in Kawempe division, Kampala, Uganda. Methods: In a community cross-sectional study, 548 study participants using random cluster sampling were enrolled. The children start lessons at 8am and end the days classes at 5pm. Random cluster sampling method was used to select participants from the 19 parishes in Kawempe district. Data was collected using a semi-structured questionnaire and Sleep Disturbance Scale for Children (SDSC). Descriptive statistics and multivariate binary logistic regression were performed with a p < 0.05 level of significance, and a 95 % confidence interval as a measure of association between the sleep disturbance. Results: Abnormal total sleep score (T- score >70) was at 3.5 %, and overall, 21.7 % of the children had an abnormal score on at least one SDSC factor. Among the children with sleep disturbances, we noted the following factors; use of an electronic device before bed, sleeping <7 h at night, having unemployed parents and lack of regular parental interaction. Conclusion: Better understanding of sleep disturbances in needed to address challenges associated with sleep among children in Uganda.